Some Approaches to Translation - Bozorova Rufina Sharopovna (Indonesian Journal of Innovation Studies, 2022)
This article discusses the art of translation and some approaches to translation. The views of some scholars on the shortcomings of the translation of a particular work and ways to overcome them are described.